Sustainability in the Pharmaceutical Industry: Solutions to Reduce Environmental Impact in Drug Production - Imam Jayanto (Journal of Pharmacopoeia, 2025)
The increase in pharmaceutical waste is a global concern due to its impact on the environment and public health. Pharmaceutical waste comes from a variety of sources, including households, healthcare facilities, and the pharmaceutical industry. This research aims to analyze the solutions needed to reduce the environmental impact in drug production. This study uses the Systematic Literature Review (SLR) method using a database from scopus. There are three stages carried out in mapping the analysis of solutions needed to reduce environmental impact in drug production, namely 1) harvesting data, 2) screening data and 3) Data Analysis and Visualization. Based on this step, seven scopus articles were analyzed. Based on research with the SLR method that has been carried out, it can be concluded that the solution to reduce environmental impact in drug production is 1) The Use of Environmentally Friendly Raw Materials, 2) Optimization of the Production Process, 3) More Effective Treatment of Pharmaceutical Waste, 4) Increased Distribution and Packaging Efficiency, 5) Stricter Environmental Regulations and Policies, and 6) Public Education and Awareness. The implications of this research are aimed at researchers and the pharmaceutical industry being more sustainable